Improving Child Oral Health: A Qualitative Study of Dental Service Provision and Enhancement Strategies - Hossein Jabbari Beyrami; Salar Mohammaddokht; Mahsa Zohdi; Milad Baseri (Taṣvīr-i salāmat)
Background. Oral health is a crucial component of general health. However, statistics and indicators have not shown improvements in dental health in Iran in recent years. Enhancing the quality of dental services in the country requires comprehensive knowledge of the current state of dental care provision. Therefore, this study aimed to evaluate dental services for children in Tabriz over the past five years and to propose strategies for improvement. Methods. This qualitative study employed a phenomenological approach and was conducted in Tabriz in 2021 (1400 Persian Calendar year). Data were collected through focus group discussions with 13 participants and semi-structured individual interviews with six participants. Among the 19 participants, 11 were general dentists, and five were pediatric dentists. Data were analyzed using Diekelmann's seven-stage phenomenological analysis method, and the main and sub-themes were categorized. Results. Six main themes and 33 sub-themes were identified. The main themes were: stewardship and leadership, service delivery, human resources, facilities and equipment, information recording, and economic issues. Seven sub-themes were found under stewardship and leadership, eight sub-themes emerged under service delivery, seven sub-themes were identified under human resources, one sub-theme was found under facilities and equipment, emphasizing their adequacy and appropriateness, five sub-themes emerged under information recording, highlighting its weaknesses, and finally, five sub-themes were identified under economic issues. Conclusion. The provision of dental equipment and facilities was identified as a major strength. However, inadequate preventive and educational dental services for children, along with deficiencies in the recording and utilization of health information, were the primary weaknesses in the delivery of dental services to children in Tabriz over the past five years.